Formulation of macro-micro safety predictors in high-rise construction sites based on dematel algorithm - Kang, Chun Xiang (2024)
The construction industry plays a pivotal role in driving national economic growth and human capital development. However, high workplace mortality rates have raised significant safety concerns, with construction accidents often linked to unsafe working conditions and worker behavior. Addressing safety compliance and safety participation is essential for improving safety performance. While previous research has focused on technological solutions, there has been little emphasis on behavioral interventions. The Theory of Planned Behaviour (TPB) provides a framework for understanding safety compliance and participation, as it posits that behavior is influenced by intention, which in turn is shaped by attitude, subjective norms, and perceived behavioral control. Despite this framework, no study has yet examined the interrelationships between safety predictors, safety compliance intention, and safety participation, particularly in the context of construction sites. This study aims to model the influence of macro and micro safety predictors on safety compliance intention and safety participation in construction projects using the Decision-Making Trial and Evaluation Laboratory (DEMATEL) technique. A total of 25 experts were invited to provide pairwise rankings of safety predictors. To ensure data reliability and consistency, 7 respondents were excluded from the final analysis, leaving feedback from 18 respondents. The study evaluated micro safety predictors (e.g., Attitude, Subjective Norm, Perceived Behavioral Control, Leadership Styles, Safety Knowledge, Safety Climate, Safety Motivation, Risk Perception, and Communication) and macro safety predictors based on Institutional Theory (e.g., Coercive, Mimetic, and Normative Pressures). The findings indicate significant relationships between all safety predictors, with “Attitude” identified as the most impactful micro safety predictor and “Coercive Pressures” emerging as the most significant macro safety predictor. The study provides valuable insights into the interrelationships between macro and micro safety predictors, safety compliance intention, and safety participation, emphasizing the need for organizations to focus on “Attitude” and “Coercive Pressures” to enhance safety performance on construction sites. Understanding these interactions is critical for developing effective interventions to improve safety outcomes in the construction industry.